Impact de la gestion foncière sur les espaces agricoles périurbaine à Madingou (Sud-Ouest du Congo) - Jean Luc Mouthou; Francelet Gildas Kimbatsa; Duck Duvais Miyalou; Létiva Craiche GOMA Mbatchi (Études Caribéennes)
In Madingou, the question of land management arises acutely, because the development of urban spaces encroaches on the lands devolved to peri-urban agriculture. This phenomenon, recognized by the municipal authorities and the populations, is at the same time at the origin of the uncontrolled growth of the city and the worrying narrowing of periurban agricultural areas. The objective of this study is to analyze the impact of land management on peri-urban agriculture in Madingou. It is conducted between January and March 2017. The methodological approach was based on documentary research and field surveys. In total, 106 households were surveyed. The results obtained from this study are characterized by a change in the built area, i.e. 121 hectares in 1946, 148 hectares in 1959, 329 hectares in 1983 and 929 hectares in 2016. After Congo's independence in 1960, the extension of the city has grown exponentially, nibbling at large farmland. This situation has resulted in an aggravated extension of the evolution of built-up areas against a reduction of agricultural areas. With regard to ongoing subdivision operations, built space will again gain in the last years nearly 178 hectares that will have been acquired at the expense of periurban agricultural areas forcing many agricultural activities to move further and further away. More around the city to settle in the villages near the urban community of Madingou.